Cation-size mismatch and interface stabilization for efficient NiOx-based inverted perovskite solar cells with 21.9% efficiency. (October 2021) - Wang, Yousheng; Ju, Hui; Mahmoudi, Tahmineh; Liu, Chong; Zhang, Cuiling; Wu, Shaohang; Yang, Yuzhao; Wang, Zhen; Hu, Jinlong; Cao, Ye; Guo, Fei; Hahn, Yoon-Bong; et al.
Abstract: Stabilization of perovskite phases and interfaces in stacked perovskite photovoltaics are critical for their efficiency, operational stability and perovskite solar modules (PSMs). Herein, A-site cation-size mismatch processed perovskite-composition films with less crystal defects are formed by incorporating larger cations formamidinium and methylammonium with smaller cations, i.e., potassium and cesium. The interface stabilization can be achieved by inserting Poly[bis(4-phenyl) (2, 4, 6-trimethylphenyl) amine], mesoporous alumina, phenethyammonium ligands and atomic-layer-deposition tin oxides at desired interfaces in inverted perovskite solar cells (PSCs). Thus, the interface defects, non-radiative recombination and ion migration can be remarkably suppressed, resulting in improvement of interface contacts and hole/electron transport. As a result, both cation-size mismatch and interface stabilization (CM-IS) strategies enable hysteresis-free, reproducible 21.9% and 16.9% efficient NiOx -based inverted PSCs and PSMs. Moreover, a high V oc of 1.16 V and 8.05 V can be obtained in large-area PSCs (1 cm 2 ) and PSMs (11.2 cm 2 ) with 7 subcells connected in series. Additionally, the measured T85 lifetime (the time as a function of PCEs decrease to 85% of its initial value) of unencapsulated PSCs under continuous AM 1.5G light illumination is approximately 1000 h. Graphical Abstract: Phase and interface defects induced non-radiative recombination and instability in inverted perovskite solar cells (PSCs) can be remarkably suppressed by A-site cation-size mismatch and interface stabilization (CM-IS) strategies. Thus, a highly efficient 21.9% and 16.9% NiOx -based inverted PSCs and perovskite solar modules (PSMs) were fabricated. Moreover, a high V oc of 1.16 V and 8.05 V can be obtained in large-area PSCs (1 cm 2 ) and PSMs (11.2 cm 2 ) with 7 subcells connected in series. ga1 Highlights: A-site cation-size mismatch processed perovskite compositional films with less crystal defects are formed. The interface stabilization is employed to reduce interface defects in stacked inverted PSCs. Inverted PSCs and modules with 21.9% (0.09 cm 2 ) and 16.9% (11.2 cm 2 ) efficiency are fabricated. Inverted PSCs based on CM-IS strategies show enhanced operational stability over 1000 h.